Estimation of Erosion Hazard Levels in the Ulakan Watershed, Padang Pariaman - Fadila Mulia Sari; Darwizal Daoed; Septi Wila Zarinda (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2026)
High rainfall can trigger flooding and riverbank erosion, particularly in flood-prone areas of Padangpariaman Regency, such as Ulakan Tapakis, Nan Sabaris, and 2x11 Enam Lingkung Districts. This study aims to estimate the level of erosion hazard based on land cover changes in 2015, 2019, and 2024. The analysis was conducted using the Universal Soil Loss Equation (USLE) method integrated with Geographic Information Systems (GIS). The estimation results indicate that the area classified under very low and low erosion categories has decreased, while the moderate, high, and very high erosion categories show a significant increase in erosion potential from year to year. This condition needs to be properly addressed to prevent the occurrence of potentially serious disasters.